PENYULUHAN DAN PELATIHAN PEMBUATAN PEWANGI PAKAIAN PADA IBU PKK DESA JONJO KECAMATAN PARIGI KABUPATEN GOWA: Counseling And Training On Making Clothes Fragrances For Mother in Family Welfare Programme, Jonjo Village, Parigi District, Gowa Regency - Sukirawati; Yusriyani; Harningsih Karim; Ermawati; Maulana Zulkarnain Imansyah; Nirwana Ibrahim; Dhandy Dharmawan; Fauzan Nursyawal; Agust Dwi Djajanti (JURNAL PENGABDIAN MASYARAKAT YAMASI, 2022)
Perfume is very familiar with everyday life to increase selfconfidence in socializing. The training for making laundry perfume in Jonjo village is aimed at making people able to make their own perfumes so that they can grow confident and can also be used as business fields. The dedication method that we do is by explaining the perfume formula followed by the practice of making pefume directly involving the service participants. Furthermore, after the laundry perfume is finished, it is packaged and then distributed to the service participants. This activity was attended by 6 AKFAR Yamasi lecturers and 3 AKFAR Yamasi Makassar students, Pak Desa Jonjo along with 5 staff and 20 PKK women in Jonjo village was very enthusiastic in participating in the training for making laundry perfume.